2020
DOI: 10.2174/1570164617666190822103329
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Development to HCV Alternate Reading Frame Protein in Liver Transplant Candidate and its Computational Analysis

Abstract: Background:: HCV Alternate Reading Frame Protein (ARFP) is a frameshift product of HCV-core encoding. Here, we characterized specific anti-ARFP antibodies in Liver Transplant Candidate (LTC) and chronic HCV-infected patients. Methods:: The ARFP gene was cloned and the recombinant protein was purified using Nickel chromatography and confirmed by western blotting. ELISA was developed using recombinant core-1a, core- 1b, ARFP-1a protein, and 99-residue synthetic ARFP 1b peptide. By several Bioinformatics tools,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Bioinformatics has provided a great context to define the structure of virus proteins (Behzad et al 2019;Dehghani et al 2017Dehghani et al , 2019aMoattari et al 2015;Zahra et al 2020). Bioinformatics tools were employed widely in this research to determine the structure of L1 and illustrated that the majority of the secondary structures belonged to the random coil and extended strand.…”
Section: Discussionmentioning
confidence: 98%
“…Bioinformatics has provided a great context to define the structure of virus proteins (Behzad et al 2019;Dehghani et al 2017Dehghani et al , 2019aMoattari et al 2015;Zahra et al 2020). Bioinformatics tools were employed widely in this research to determine the structure of L1 and illustrated that the majority of the secondary structures belonged to the random coil and extended strand.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been reported that PFDN2 plays an important role in the development of chronic HCV infection and liver disease. 31 The long-term hepatitis can cause liver cancer, so there may be some interaction between PFDN2 and liver cancer to affect tumors. Recent studies have found 32 that various subunits of PFDN have a high affinity with HDAC1 in hepatocellular carcinoma HepG2 cells, which further provides a basis for this hypothesis.…”
Section: Pfdn2 Can Be Used As a Tumor Biomarkermentioning
confidence: 99%
“…2.3. InvH physicochemical properties "Expasy's ProtParam" (http://expasy.org/ tools/protparam.html) was used to determine theoretical isoelectric point (pI), instability index, aliphatic index, and grand average hydropathy (GRAVY) [17][18][19].…”
Section: Amino Acid Changing and Phylogenetic Treesmentioning
confidence: 99%